TASTE MASKING: BY ION EXCHANGE COMPLEXATION TECHNIQUE - Madhuri, Bhalerao; Khutle, Nilesh (Asian Journal of Pharmaceutical Research and Development, 2016)
Organoleptic properties such as taste, smell and texture are also the important factors in development of oral dosage forms. Taste is one of the major factors which affect the patient compliance and product quality. Acceptability of any drug dosage form mainly depends over its taste i.e. mouth feel .drug molecule interacts with taste receptor on the tongue to give bitter, sweet or other taste sensation, when they dissolve in saliva. This sensation of taste is the result of signal transduction from the receptor organs for taste, commonly known as taste buds. Now a days most of the potent drugs that may be cardiac, analgesics, anti-inflammatory, antitubercular, anthalmentics , antibacterial ,anticoagulants, anti-epileptics, antimalarials, anti neoplastics, anti-thyroids, antiprotozoal, diuretics,histamine receptor antagonists, nutritional agents, opioids analgesics, oral vaccines and sex hormones , most of them are bitter in taste. So it becomes necessary to develop such a dosage for that must be acceptable in taste to patient especially in case of children or geriatrics. Masking of bitter and obnoxious taste of drugs in paediatric and geriatric formulations is a challenge to the pharmacist to ensure patient compliance and product value where the process and formulation should be economic, rapid and easy, involve least number of equipment, processing steps and minimum number of excipients without adverse effect on drug bioavailability.